Analysis of dividend policy in the banking sector of 3 ASEAN countries - Mutmainna Mutmainna; Farah Margaretha Leon (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study investigates the determinants of dividend policy in the banking sector across Indonesia, Singapore, and Malaysia by examining the effects of profitability, growth opportunities, valuation, liquidity, bank size, and credit risk. Using panel data regression analysis, the study analyzes 102 bank-year observations from 17 conventional banks based on annual financial reports. The findings reveal that profitability, measured by Return on Assets (ROA), and bank size exert a positive and significant influence on dividend policy, indicating that larger and more profitable banks are more likely to distribute higher dividends to shareholders. In contrast, liquidity and non-performing loans (NPLs) demonstrate significant negative effects, suggesting that banks facing greater liquidity pressures or higher credit risk tend to retain earnings rather than increase dividend payouts. Meanwhile, market-to-book value and price-to-earnings ratio do not significantly affect dividend policy decisions. These results highlight the importance of internal financial performance and risk management in shaping dividend distribution strategies within the banking industry. The study contributes to the literature on banking finance by providing comparative evidence from Southeast Asian banking markets and offers practical insights for managers, investors, and policymakers regarding dividend policy formulation in a dynamic financial environment. Keywords: Bank Size; Dividend Policy; Liquidity; Market to Book Value; Non Perfoming Loan; Price/Earning Ratio; Return on Asset